Effect of drying temperatures on chemical and morphological properties of acorn flours (International Journal of Food Science & Technology, 2009)
Drying curves at diﬀerent temperatures were established for Quercus suber and Quercus rotundifolia fruits. Flours produced by milling fruits dried at diﬀerent conditions were evaluated for colour, starch granules morphology, amylose and sugars content. The drying temperature was positively related to the reducing sugar content and negatively to starch content. The amilose content generally increased with drying temperature and the eﬀect was more evident for the Q. rotundifolia. Results showed that ﬂour colour parameters generally decreased with increased drying temperature. However, the drying temperature does not seem to aﬀect starch morphology. It can also be stated that Q. suber produced darker ﬂours, higher amylose and reducing sugar content, and bigger starch granules. Q. rotundifolia showed a lower level of damaged starch and higher fat and disaccharides content. According to the results, it was possible to conclude that drying temperature exerted marked eﬀects on the properties of acorn ﬂours in both studied species.

Effect of drying temperatures on chemical and morphological properties of acorn flours - Correia, Paula R.; Leitão, António E.; Beirão-da-Costa, Maria L. (International Journal of Food Science & Technology, 2009)
Drying curves at diﬀerent temperatures were established for Quercus suber and Quercus rotundifolia fruits. Flours produced by milling fruits dried at diﬀerent conditions were evaluated for colour, starch granules morphology, amylose and sugars content. The drying temperature was positively related to the reducing sugar content and negatively to starch content. The amilose content generally increased with drying temperature and the eﬀect was more evident for the Q. rotundifolia. Results showed that ﬂour colour parameters generally decreased with increased drying temperature. However, the drying temperature does not seem to aﬀect starch morphology. It can also be stated that Q. suber produced darker ﬂours, higher amylose and reducing sugar content, and bigger starch granules. Q. rotundifolia showed a lower level of damaged starch and higher fat and disaccharides content. According to the results, it was possible to conclude that drying temperature exerted marked eﬀects on the properties of acorn ﬂours in both studied species.
Keywords: Acorn (Quercus suber and Quercus rotundifolia); chemical properties; drying; morphology